EFFECT OF DIFFERENT CONCENTRATIONS OF ASCORBIC ACID ON SEMEN QUALITY AND HATCHABILITY OF INDIGENOUS ASEEL CHICKEN - A. Jabbar; W. Abbass; A. Riaz; A. Sattar; M. Akram (Journal of Animal and Plant Sciences, 2015)
Aseel, a famous chicken breed, has problems of low fertility that leads to poor hatchability. In commercial breeder setups, the hatchability issues are being addressed by fresh semen artificial insemination (AI). The success of AI mainly depends on semen quality and its life in female reproductive tract. Now a days, different antioxidants are being used to improve the semen quality. This study was designed to optimize the ascorbic acid addition, in semen extender, as an antioxidant. Semen from twenty roosters was collected by abdominal massage. After pooling, the semen was extended in modified ringer’s solution (1:3) supplemented with different concentrations of ascorbic acid (0, 0.25, 0.5, 0.75, 1, 1.25 and 1.5% w/v). For longevity testing, in-vitro sperm parameters (motility, live ratio and morphology defects) were evaluated, at 0, 6, 12, and 24 h intervals during storage at 4°C. The protection of ascorbic acid against oxidative stress was evident within 6 h storage by semen motility improvement, (69% in 1% ascorbic acid vs 63% in control; p<0.05). Similarly, for sperm live ratio, the difference became clear within 6 h (80% for 0.75, 1, 1.25% vs 72% for control; p<0.05). After 24 h storage, the improvements, in 1% ascorbic acid samples, became more evident (p<0.05) in terms of motility, live sperm and morphological defects. However, the higher concentration of ascorbic acid (1.5%) showed compromised results. This represents the toxic effect of ascorbic acid on higher concentrations. To access our final target, for hatchability improvement, 100 Aseel hens were inseminated with semen. Total hens were divided in two groups and inseminated with best supplemented (1% ascorbic acid) or control (0% ascorbic acid) semen. The supplemented semen enhanced egg hatchability (55% vs 45%; p>0.05). These results indicate that the success rate of AI can be improved by using 1% ascorbic acid in poultry semen extender.
Keywords: Ascorbic acid; Indigenous Aseel chicken; Semen quality; Hatchability